School Libraries and Educational Development in Nigeria: Issues and Prospects - Esan, Adedoyin Oluwatosin (Department Library of Governance Institut of Home Affairs, 2022)
Background: The National policy of education of Nigeria indicated the importance and need to have functional school libraries, but the situation over the years later is worrisome as many researchers have reported the non-existence of library in many schools and the deplorable state of the ones available. This is hampering the role expected to be played by school libraries in the development of education in Nigeria. Purpose: The research explores the various challenges confronting school libraries and proffer workable solutions. Method: This paper uses literature review as a methodology for conducting research. The literature reviewed exposed the current state of school libraries, the challenges, prospects and the services that can help promote educational developments in school libraries. Result: The findings revealed the challenges limiting school libraries to include inadequate funding, lack of trained personnel, non-compliance to the provisions in the National Educational Policy and the absence of dedicated library time. Possible solutions include library advocacy, ensuring the implementation of the National Educational Policy, enforcing the appointments of trained personnel, developing standard benchmark for establishing and management of school libraries and the introduction of dedicated library time. Conclusion: The paper recommended that LRCN and NLA should constantly advocate for quality service delivery in school libraries through ensuring strict compliance with the provisions in the National Policy of Education by forming accreditation committee to monitor all schools. It was also recommended that the Library and Information Science curriculum be reviewed to include innovative library services that can be adopted to improve reading habits in schools. Keywords: School libraries; Educational Development; Reading Habits; National Development